Hubungan Laba Akuntansi, Nilai Buku, dan Total Arus Kas dengan Market Value: Studi Akuntansi Relevansi Nilai - linda linda; fazli syam bz. (The Indonesian Journal of Accounting Research, 2013)
The objective of this study is to prove value-relevance of earnings, book value and total cash flows compared to other information that are used by investors in decision making, in stressing on the price model and the return model. Although their theoretical foundations are the same, the results obtained using these two models are sometimes inconsistent. In some research contexts the combined  use of both price and return models may be useful for the purpose of assessing the accounting information usefulness in equity valuation.The sample cover 58 companies which are selected by using stratified random sampling method for non financial companies populations (except infrastructure, utility, transportation sector and trading, service, investment sector). Those selected companies announced their financial statement between January 1st – July 31st in 1997 to 2002.Based on the price model, the study shows that value-relevance from accounting information variables have significant moderate and stable level of correlation during observation, so its variable may explain the investors expectation in the future. Based on the return model,it shows that the decreasing of value-relevance of accounting information variables have been observed, but they have been not significant. This fact that the variables have been anticipated by the market before information announced.